Standardized coronectomy versus total extraction for impacted mandibular third molars: a single-blinded prospective analysis of patient-reported outcomes - Khalid Al-Ali; Roba Saqan; Sarah Alkhazraji; Kamis Gaballah (Frontiers in Oral Health)
IntroductionCoronectomy is proposed as an alternative to surgical extraction for impacted mandibular third molars, particularly in cases with an elevated surgical risk of inferior alveolar nerve injury. However, this procedure is not widely adopted by many surgeons due to concerns about potential complications and the perception that patients may be less likely to accept this treatment option.MethodsThis cross-sectional, prospective, single-blinded study compared patient-reported outcomes between standardized coronectomy and extraction of impacted mandibular third molars in 70 patients (aged 19–55 years) using the Postoperative Symptom Severity (PoSSe) scale.ResultsWhile coronectomy avoided nerve injury, it resulted in relatively longer recovery times (40% vs. 28.6% requiring ≥5 days) and prolonged medication use (34.3% vs. 14.3% >5 days) compared to extraction. Coronectomy patients reported significantly higher pain and swelling scores, particularly among females (>25 years), though neither procedure adversely affected eating, speech, or quality of life. Gender and age influenced outcomes, with females and older patients experiencing more pronounced postoperative morbidity after coronectomy.DiscussionThese findings underscore the need for demographic-specific counseling and tailored postoperative care when selecting coronectomy. Further research with larger sample sizes is recommended to validate these findings and optimize decision-making for mandibular third molar surgeries.